Effect of behavioral health services and neighborhood disadvantages on recidivism: a comparison of mental health court and traditional court participants - Han, Woojae (Journal of experimental criminology, 2020)
This study investigates the impact of behavioral health services and neighborhood disadvantage on recidivism among offenders with mental illness in mental health courts (MHCs) and in traditional courts. Although treatment is believed to lead to reduced recidivism for offenders with mental illness, little research has been conducted with MHC participants. Furthermore, neighborhood disadvantages are known to influence recidivism generally, but environmental factors have not been examined in the MHC context.